HUBUNGAN ANTARA KONTROL DIRI DENGAN PERILAKU KONSUMTIF PENGGUNAAN KUOTA INTERNET SAAT PANDEMI COVID-19 PADA SMPIT QURRATA A’YUN BATUSANGKAR - Irvan Kurnia; Rosmawati Rosmawati; Donal Donal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The problem in this study is the consumptive behavior of students towards using internet quotas excessively and not for what they need, Using internet quotas to seek pleasure, which most students get nothing from using internet quotas other than just looking for fun, so they cannot control themselves to do things. something that is more useful than just looking for fun from using the internet, the large number of students who use the internet cannot be separated from the large internet quota used. The purpose of this study was to determine whether there was a significant correlation between self-control and consumptive behavior in the use of internet quota during the Covid-19 Pandemic at SMPIT Qurrata A’Yun Batusangkar. This research is a quantitative method of correlational type. Sampling using Cluster Sampling, with a population of 153 students, and a sample of 44 people. The data were collected by spreading the Likert Scale. The data analysis technique used Product Moment. negative and significant relationship between self-control and student consumptive behavior. This means that the higher the student's self-control, the lower the student's consumptive behavior, on the contrary, the lower the student's self-control, the higher the student's consumptive behavior.Key Words: Self Control, Consumptive Behavior, Internet Quota